Estudo do conversor bosst CC-CC de alto ganho de tensão baseado na célula de comutação de três estados e nas células multiplicadoras de tensão (MC) - Alcazar, Yblin Janeth Acosta (2010)
The present work proposes the study of the boost converter based on three-state switching cell and voltage multipliers cells (mc). A mathematical model of the aforementioned converter is investigated here. The proposed analysis is based on the tool named “PWM-Switch Modeling of DC-DC Converters”. The model must be found by a simple inspection of the converter’s circuit. It is possible to apply such model in order to realize various analyses such as steady-state, transient, and small-signal analysis in a single and same model. Considering the number of voltage multipliers cells (mc), two situations are analyzed: operation with a single multiplier cell (mc=1) and operation with multiple voltage multiplier cells (mc>1).The proposed method was validated through simulations and its effectiveness was verified. In addition to this, conventional average current mode control is also applied to one of the studied configurations. The performance of the converter and the effectiveness of the proposed controller are demonstrated by experimental results obtained from a 1-kW laboratory prototype.